Internet literacy among the elderly in Thailand. Issue 3 (3rd July 2021) - Diteeyont, Watsatree; Ku, Heng-Yu
ABSTRACT: The elderly benefit from using the Internet for various purposes, and achieving Internet literacy is essential for their participation as digital citizens. This study investigates the levels and influential factors of Internet literacy among 534 elderly in Thailand. The results showed that the participants had an intermediate level of Internet literacy overall. Most of the elderly had solid knowledge and skills in using digital tools and applying strategies to obtain information from reliable resources online. They could also communicate and protect their personal information on online platforms. However, some of the participants lacked experience and skills in identifying spam emails, and they neglected to report illegal online content and violence to the relevant government sectors. The participants' Internet literacy levels did not vary by profession, frequency of internet access, and amount of time spent online per day. Instead, it was affected by education level, device type, and length of experience using the Internet. Future studies may focus on developing effective strategies to help senior citizens obtain higher levels of Internet literacy and explore qualitative data on their attitudes, needs, and concerns about Internet use, to build a safe Internet environment for elderly users.